Contexte socio-culturel et écologique des mangroves du Vietnam durant la première moitié du xxe siècle selon Eugène Poilane - Ariadna Burgos; Benoît Carré; Françoise Aubaile-Sallenave; Sovanmoly Hul (Revue d'ethnoécologie)
In the last few decades, the mangroves ecosystems in Vietnam have been strongly affected by various factors: spraying of Agent Orange during the war, monoculture, urbanization, development of intensive shrimp farming, as well as coastal erosion and climate change. During the first half of the 20th century, Eugène Poilane – the most prominent collector of Indochinese flora – explored and surveyed various types of forest ecosystems throughout French Indochina, including various mangrove ecosystems. The work and observations carried out by this intrepid and courageous naturalist is of remarkable rigor and meticulousness. Eugène Poilane’s work – his botanical specimens, manuscripts and fieldwork notebooks – help us trace the floristic diversity of mangrove species, their abundance and distribution. It also provides detailed information about indigenous knowledge and uses of the various species, the operational management and economic value of mangroves, all within the unique socio-cultural and environmental context of the French colonial era in southeast Asia. His observations, from 1919 to 1941, suggest that the mangroves were already strongly modified by humans in the begining of the 20th century: a sort of anthropized landscape. Eugène Poilane leaft an unparalleled scientific heritage and unpublished documentation that can be exploited by anyone interested not only in the floristic diversity of French Indochina, but also in the evolution of these ecosystems, the uses of plant species, as well as the socio-cultural, economic and political transformations of these environments.